The effect of moderate versus high intensity exercise on heart rate variability in sedentary office workers - Gangwar, Vibha; Verma, Manish Kumar; Gangwar, Ritesh Singh; John, Nitin Ashok; Jasrotia, Rajani Bala (Journal of Bangladesh Society of Physiologist, 2021)
Background: Sedentary behavior is one of the leading modifiable risk factors for cardiovascular disease and all-cause mortality. Physical exercise exerts beneficial physiological effects on cardiovascular fitness. Different grades of physical exercise have different effects on cardiovascular health. Objective: To compare the effect of moderate and high intensity exercise training on heart rate variability (HRV) in sedentary office workers. Methods: This study was conducted on 40 healthy sedentary volunteers aged between 20-40 years of both the genders. Participants were distributed into two groups of 20 subjects each. Subjects of group I and group II performed moderate intensity and high intensity exercise respectively on bicycle ergometer for 12 weeks. Their 5- minute ECG recording was done by three channel physiograph, and frequency domain indices of HRV and heart rate (HR) were analyzed and compared before and after exercise training. Their blood pressure was also recorded and compared before and after exercise training. Independent sample t-test and paired sample ttest were used for statistical analysis. Results: HF, systolic and diastolic blood pressure reduced significantly after exercise in group II (p=0.015, 0.005, and 0.015 respectively) while HR and LF/HF ratio reduced in both group I and group II (p=0.000 for HR, and 0.034, 0.001 for LF/HF). The decrease in HR was greater after high intensity exercise than moderate intensity exercise (p= 0.025). Conclusion: Parasympathetic activity improves after moderate and high intensity exercise but improvement is more after high intensity exercise training. Therefore, high intensity exercise training is more beneficial than moderate intensity exercise training. J Bngladesh Soc Physiol 2021;16(1): 16-23